AB0971 A CASE OF PEDIATRIC IDIOPATHIC CALCINOSIS. (June 2019) - Gamalero, Lisa; Pagnini, Ilaria; Simonini, Gabriele; Cimaz, Rolando; Giani, Teresa
Abstract : Background: Calcinosis includes a rare group of disorders characterized by abnormal intracutaneous, subcutaneous, fascial or intramuscular calcium deposits. Idiopathic calcinosis is diagnosed after the exclusion of secondary forms related to trauma, abnormal calcium/phosphorus metabolic disorders, inflammatory processes, neoplasms, connective tissue diseases or renal insufficiency. There are very few cases reported, especially in childhood. Objectives: We report the case of idiopathic calcinosis cutis in a young girl. Methods: A 15-year-old female presented an abrupt onset of 2 painful swollen lesions on the left trochanteric region and over the posterior side of her right elbow. The patient denied any trauma or associated symptoms such as muscle weakness or joint stiffness. On physical examination, a large hard mass was present over her left trochanteric region, with hyperemic skin, and a similar one was palpable over her right elbow. Results: Radiographs of the two sites showed well-defined calcified masses, one (9x5 cm) over the trochanteric region, and the other (3x2) cm over the posterior aspect of the distal end of the humerus extending up to the elbow. MRI confirmed the presence of calcified intramuscular lesions (Figure 1 ). Serologic evaluation showed increased levels of CRP and ESR, while autoimmune screening was negative. Calcium/phosphorus metabolism, creatinine kinase, aldolase and ferritin levels were within the normal limits. Therefore, a clinical diagnosis of idiopathic calcinosis was made. After 3 months, the lesion on the elbow had spontaneously reabsorbed, while the other one kept on growing, with 3-4 episodes per month of febrile painful swelling. A CT-guided biopsy was then performed, confirming the diagnosis of calcinosis. No infectious causes were detected. One year later, since there was no local amelioration, the lesion was surgically removed with apparent complete local remission. No other new lesions were detected during the 3 months follow-up period. Conclusion: Idiopathic calcinosis is very rare and no specific medical therapies are available. In our patient no causative factors were identified and thus the diagnosis of idiopathic calcinosis was made. Prognosis seems to be variable, since one lesion risolved spontaneously while the other needed surgical excision. References: [1] Alabaz D, Mungan N, Turgut M, Dalay C: Unusual Idiopathic Calcinosis Cutis Universalis in a Child. Case Rep Dermatol2009;1:16-22. doi: 10.1159/000227285 [2] N. Reiter, L. El-Shabrawi, B. Leinweber, A. Berghold, and E. Aberer, "Calcinosis cutis. Part I: diagnostic pathway, "Journal of the American Academy of Dermatology, vol. 65, no. 1, pp.1–12, 2011. [3] [3] Hwang ZA, Suh KJ, Chen D, Chan WP, Wu JS. Imaging Features of Soft-Tissue Calcifications and Related Diseases: A Systematic Approach. Korean J Radiol. 2018Nov-Dec;19(6):1147-1160. [5] S. K. Venkatesh Gupta, Ramana Rao Balaga, and Suman Kumar Banik, "Idiopathic Calcinosis Cutis over Elbow in a 12-Year Old Child, "Case Reports in Orthopedics, vol. 2013, Article ID 241891, 4 pages, 2013. Disclosure of Interests: Lisa Gamalero: None declared, Ilaria Pagnini: None declared, Gabriele Simonini Grant/research support from: Abbvie, Speakers bureau: Abbvie, Rolando Cimaz: None declared, Teresa Giani: None declared